Recommendations of the Colombian consensus committee for the management of traumatic brain injury in prehospital, emergency department, surgery, and intensive care (beyond one option for treatment of traumatic brain injury: a stratified protocol [BOOTSTRAP]) (2020)
Traumatic brain injury (TBI) is a global public health problem. In Colombia, it is estimated that 70% of deaths from violence and 90% of deaths from road traffic accidents are TBI related. In the year 2014, the Ministry of Health of Colombia funded the development of a clinical practice guideline (CPG) for the diagnosis and treatment of adult patients with severe TBI. A critical barrier to the widespread implementation was identified—that is, the lack of a specific protocol that spans various levels of resources and complexity across the four treatment phases. The objective of this article is to present the process and recommendations for the management of patients with TBI in various resource environments, across the treatment phases of prehospital care, emergency department (ED), surgery, and intensive care unit. Using the Delphi methodology, a consensus of 20 experts in emergency medicine, neurosurgery, prehospital care, and intensive care nationwide developed recommendations based on 13 questions for the management of patients with TBI in Colombia. It is estimated that 80% of the global population live in developing economies where access to resources required for optimum treatment is limited. There is limitation for applications of CPGs recommendations in areas where there is low availability or absence of resources for integral care. Development of mixed methods consensus, including evidence review and expertise points of good clinical practices can fill gaps in application of CPGs. BOOTStraP (Beyond One Option for Treatment of Traumatic Brain Injury: A Stratified Protocol) is intended to be a practical handbook for care providers to use to treat TBI patients with whatever resources are available. Stratification of recommendations for interventions according to the availability of the resources on different stages of integral care is a proposed method for filling gaps in actual evidence, to organize a better strategy for interventions in different real-life scenarios. We develop 10 algorithms of management for building TBI protocols based on expert consensus to articulate treatment options in prehospital care, EDs, neurological surgery, and intensive care, independent of the level of availability of resources for care.